THE STUDY OF THE MINERAL CHEMICAL COMPOSITION OF THE YAKUT SAPONITE MINERAL AND THE PHYSICO-CHEMICAL BASES OF COMPLEX TRACE ELEMENTS - Tursunova Firuza Jamshidovna (American Journals, 2022)
The conducted chemical studies show that in the selected saponites of the upper layer the content of chemical elements is CAO - 22.57%; MdO - 20.99; SiO2 - 26.30; K2O - 1.23% and Fe2O3 - 7.92% and in the lower layer the content of chemical elements is CaO2 1.48%; MgO - 19.75; SiO2 - 27.41; K2O - 1.31% and Fe2O3 - 8.23%. . The mass loss when the saponite sample is heated to 1000 °C is 9.87%. The endoeffects in the range of 90-160 °C correspond to the removal of adsorbed water on the inner surface of the intercrystal minerals that make up saponite. Endoeffects in the range 160-330°C correspond to the beginning of the removal of constitutional water minerals A further increase in temperature is also accompanied by dehydration of mineral impurities.
Keywords: saponite, analcime, smectite mineral composition, exchange capacity of cations.dolomite